Running Distance Is Associated With Components of Total Energy Expenditure in Amenorrhoeic and Non‐Amenorrhoeic Endurance Runners - Akiko Uchizawa; Emi Kondo; Yasushi Enomoto; Katsuhiko Yajima; Shinsuke Tamai; Koichi Watanabe; Ai Ito; Miki Kosugi; Yasuki Higaki; Hiroyuki Sagayama (Scandinavian Journal of Medicine & Science in Sports, 2026)
ABSTRACT Some competitive runners strategically regulate their body weight to optimize race performance by balancing energy intake and expenditure. The constrained total energy expenditure (TEE) model suggests that exercise energy expenditure (EEE) is sustained through compensatory reductions in other components of TEE, including resting metabolic rate (RMR) and sleeping metabolic rate (SMR). However, it remains unclear whether TEE and its components differ between athletes with and without amenorrhoea, or whether the constrained energy model applies to athletes engaged in chronic training. This study compared TEE components—SMR, RMR, non‐exercise activity thermogenesis (NEAT), and EEE—between amenorrhoeic and non‐amenorrhoeic runners and examined their relationship with physical activity, particularly weekly running distance. Twenty female middle‐ and long‐distance runners (10 amenorrhoeic and 10 non‐amenorrhoeic) participated. TEE and body composition were measured under free‐living conditions using the doubly labeled water method, while RMR and SMR were assessed in a whole‐room metabolic chamber. NEAT was estimated by accelerometry and training reports, and EEE was calculated by subtraction. TEE and its components did not differ between amenorrhoeic and non‐amenorrhoeic runners. Weekly running distance did not correlate with TEE but was negatively linked to NEAT and positively to EEE, whereas its negative associations with RMR and SMR were attenuated after adjustment for body composition. Similar directional associations were observed in both groups, but the study was not powered to test effect modification by menstrual status. These findings are consistent with the constrained TEE model and suggest that higher training volume may be accompanied by a reallocation of energy expenditure among its components in chronically trained runners.